Struktur Gerak Tari Tampuruang Di Nagari Batu Manjulua Kecamatan Kupitan Kabupaten Sijunjung Provinsi Sumatera Barat - Nadya Putri Yolanda; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2021)
This study aims to describe and analyze the motion structure of Tampuruang dance in Batu Manjulua village, Kupitan district, Sijunjung regency, West Sumatra province. This research belongs to a qualitative research. The types of data used were primary and secondary data. The main instrument in this research was the researcher itself and was assisted by supporting instruments such as writing tools, cameras, and flash drives. The data were collected through literature study, observation, interview, and documentation. The steps of analyzing the data was collecting the data, describing the data, and concluding the data. The results show that 1) related to the relationship system of basic elements, Tampuruang Dance has motions of body parts consisting of the head, body, hands, and feet. From the relationship system between the elements above, it produces the form of motives which are alternate and interrelated like a chain, 2) Related to the hierarchical grammatical relationship system, Tampuruang Dance consists of 42 motifs, 8 phrases, 5 sentences, and 1 cluster, 3) Tampuruang dance belongs to a syntagmatic relationship system which is like a chain, and it cannot be separated or exchanged between one another.